2011
DOI: 10.1038/srep00137
|View full text |Cite
|
Sign up to set email alerts
|

Galantamine improves olfactory learning in the Ts65Dn mouse model of Down syndrome

Abstract: Down syndrome (DS) is the most common form of congenital intellectual disability. Although DS involves multiple disturbances in various tissues, there is little doubt that in terms of quality of life cognitive impairment is the most serious facet and there is no effective treatment for this aspect of the syndrome. The Ts65Dn mouse model of DS recapitulates multiple aspects of DS including cognitive impairment. Here the Ts65Dn mouse model of DS was evaluated in an associative learning paradigm based on olfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Studies in the SVZ, the RMS and the olfactory bulb have revealed a reduction in cell proliferation in the Ts65Dn mice model (Chakrabarti et al, 2011 ; Bianchi et al, 2014 ). Moreover olfactory learning is impaired in Ts65Dn mice (de Souza et al, 2011 ), similarly to the observed impairment in olfactory performance in adult with DS (Nijjar and Murphy, 2002 ). Activation of the olfactory system by odor exposition doesn't affect the number of proliferating cells; however the number of survival cells in the olfactory bulb is increased (Rochefort et al, 2002 ).…”
Section: Introductionmentioning
confidence: 54%
“…Studies in the SVZ, the RMS and the olfactory bulb have revealed a reduction in cell proliferation in the Ts65Dn mice model (Chakrabarti et al, 2011 ; Bianchi et al, 2014 ). Moreover olfactory learning is impaired in Ts65Dn mice (de Souza et al, 2011 ), similarly to the observed impairment in olfactory performance in adult with DS (Nijjar and Murphy, 2002 ). Activation of the olfactory system by odor exposition doesn't affect the number of proliferating cells; however the number of survival cells in the olfactory bulb is increased (Rochefort et al, 2002 ).…”
Section: Introductionmentioning
confidence: 54%
“… 110 Based on the hypothesis that donepezil might prevent the loss of ChAT seen in the BFCN of Ts65Dn mice after ~6 months of age, and therefore it would prevent or rescue some cognitive impairment, 4-month-old male Ts65Dn mice were treated for 7 weeks with donepezil; no improvement was seen in acquisition in the MWM. 31 This contrasts with the positive effects of the other anticholinesterases, physostigmine and galantamine, 60 , 61 discussed earlier, that rescued learning deficits in Ts65Dn of similar age (in the case of physostigmine with a single injection 60 ). However, the structure of donepezil is not related to those of other acetylcholinesterases and, in addition, the effects of donepezil in other mouse models have been sensitive to dose and have not been completely consistent.…”
Section: Ts65dn and Preclinical Evaluation Of Drug Efficacymentioning
confidence: 68%
“…In a second study, galantamine was used with an olfactory test of L/M. 61 This test was also chosen because it is nonaversive, and because it exploits a normal sensory drive that is particularly strong in rodents. Furthermore, there are data showing that people with DS have impaired olfaction, even at young ages, 62 and that the impairment increases with age.…”
Section: Ts65dn and Preclinical Evaluation Of Drug Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Galantamine [19,[53][54][55] A competitive, rapidly reversible potent AChE inhibitor, galantamine was approved in AD therapy in 2001. It is well absorbed with an 85% to 100% bioavailability in oral delivery.…”
Section: Traditional Cheismentioning
confidence: 99%